Dendritic Cells from HIV-1 Infected Individuals are Less Responsive to Toll-like Receptor (TLR) Ligands (2007)
ABSTRACT: We compared TLR responsiveness in PBMC from HIV-1-infected and uninfected individuals using the TLR agonists: TLR7 (3M-001), TLR8 (3M-002), and TLR7/8 (3M-011). Activation and maturation of plasmacytoid dendritic cells (pDC) were measured by evaluating CD86, CD40, and CD83 expression and myeloid dendritic cell (mDC) activation was measured by evaluating CD40 expression. All agonists tested induced activation and maturation of pDC in PBMC cultures of cells from HIV+ and HIV- individuals. The TLR7 agonist induced significantly less pDC maturation in cells from HIV+ individuals. Quantitative assessment of secreted IFN-alpha and pro-inflammatory cytokines at the single cell level showed that pDC from HIV+ individuals stimulated with TLR7 and TLR7/8 induced IFN-alpha. TLR8 and TLR7/8 agonists induced IL-12 and COX-2 expression in mDC from HIV+ and HIV- individuals. Understanding pDC and mDC activation and maturation in HIV-1 infection could lead to more rational development of immunotherapeutic strategies to stimulate the adaptive immune response to HIV-1.